School factors and student drinking in high schools: a cross-sectional study of school policies and party regulation - Veronica S. C. Pisinger; Pernille Bendtsen; Morten Hulvej Rod; Janne S. Tolstrup (BMC, 2020)
Abstract Background The effectiveness of school alcohol polices may be affected by the degree of strictness of rules, how they are implemented and enforced, students' perception of the rules and the consequences of breaking them. The aim of the study was to test the hypothesis that more liberal school alcohol policies, lack of knowledge of the alcohol policy, lower prices of alcohol at school parties, and liberal party regulation were associated with more drinking among high school students. Methods Participants were high school students (n = 68,898), participating in the Danish National Youth Study in 2014. Data came from questionnaires answered by high school students and school headmasters. Zero-inflated negative binominal regression with clustering of schools (n = 117) was used to assess the associations between alcohol policy reported by school headmaster and weekly alcohol intake reported by students. Multilevel negative binominal regression was used to assess the associations between alcohol price and liberal party regulations and units consumed at the last school party and units consumed at the school during the last school party. Results In general, school alcohol policies were not associated with high school students' weekly alcohol intake. High school students who did not know the school alcohol policy had a higher weekly alcohol intake (0.16 drinks 95% CL [0.11;0.21] p = 0.000), compared to students who knew the policy. Lower beer prices were positively associated with the number of drinks consumed at the school (p = 0.004), but not with the total amount consumed at the last school party (p = 0.728). High school students who agreed that students who were drunk could buy alcohol had a higher alcohol intake at the last school party (OR = 0.20 drinks 95% CL [0.18;0.21], p < 0.001) and drank more at the school (0.17 drinks 95% CL [0.15;0.18], p < 0.001) compared to those who did not agree that students who were drunk could buy alcohol. Conclusion School alcohol policies were generally not associated with drinking among high school students, whereas students' lack of knowledge of the school policy was associated with a higher weekly alcohol intake. An addition, lower prices and liberal party regulation was associated with higher alcohol intake at school parties.